The power of brand ambassador Twice influences brand image and purchase intention on Scarlett Whitening beauty products - Rosari, Theodora Lady; Simamora, Bilson (Business and Entrepreneurship Department, Kwik Kian Gie School of Business and Information Technology, Jakarta, 2024)
Previous studies have shown inconsistent results regarding brand ambassadors' influence on purchase intention. This study aims to determine the power of brand ambassadors in influencing brand image and purchase intention of beauty products. This research replicates Oktaviani and Zainurossalamia's (2021) model by differentiating the research context and using the concept of brand ambassadors, brand image, and purchase intention. With Scarlett Whitening's products in mind, the data were collected using questionnaires distributed through Google Forms to 151 respondents selected judgmentally from customers who ever bought and used Scarlett Whitening. Using Structural Equation Modeling (SEM) to analyze the data with the help of WarpPLS 8.0, the study found that brand ambassadors' power positively influences brand image and purchase intention. The author suggests companies consider adding product variants for other skin types. Future researchers can add or use different variables to enrich these research findings.